(untitled) (Journal of Medical & Health Sciences Review, 2025)
Tuberculosis (TB) is a significant global health challenge, particularly in low- and middle-income countries (LMICs) like Pakistan. Despite high awareness, sociocultural myths and misconceptions about TB persist. Therefore, this study aims to explore the knowledge and sociocultural beliefs regarding TB among the rural population of Lakhodair, Lahore, Pakistan. A quantitative descriptive cross-sectional design was employed. Data were collected from 109 permanent residents of Lakhodair using a structured questionnaire. The sample included participants aged 16 and above, both male and female, using non-probability convenient sampling. SPSS version 20 was used for data analysis. The findings reveal a high level of awareness about TB, with 79.8% of participants recognizing TB as a disease and 94.5% and 97.2% acknowledging its preventability and curability respectively. However, significant misconceptions remain, particularly regarding the treatment and prevention of TB influenced by sociocultural beliefs. Notably, 58.7% agreed that TB cannot be cured in hospital/health center, 67% believed health workers could infect others with TB and 68.8% believed in the hereditary nature of the TB. While awareness of TB in the Lakhodair community is commendably high, persistent misconceptions due to sociocultural beliefs need addressing. Effective TB control requires targeted health education that incorporates cultural contexts and builds trust in healthcare systems. Future initiatives should focus on correcting these misconceptions to improve TB outcomes in rural areas.